Shaping ability of NiTi reciprocating file systems R-motion and waveOne gold in mesial canals of mandibular molars; micro CT study - Mona Alsulaiman; Loai Alsofi; Mey A. Alhabib (Scientific Reports)
Abstract The preservation of the original configurations of root canals during endodontic preparation is crucial for treatment success. Nickel-titanium (NiTi) rotary systems have been refined to optimize canal shaping while minimizing iatrogenic errors. This study aimed to evaluate and compare the shaping efficacy of the novel R-Motion (RM) and the established WaveOne Gold (WG) systems using micro-computed tomography (micro-CT). Twenty-four mesial canals of 12 double-rooted extracted mandibular first molars were randomly assigned to either the RM or WG groups, with the mesiobuccal (MB) and mesiolingual (ML) canals allocated accordingly. Root canals were prepared following the manufacturer’s protocols. In the RM group, crown-down technique up to a 25/0.06 taper was employed. For the WG group, the preparation was completed with a WG primary file (25/0.07 taper). Specimens were scanned using micro-CT scans before and after instrumentation to establish baseline and post-instrumentation datasets. The following parameters were evaluated, and values were calculated to compare the shaping ability of the two files: percentage of untouched canal walls, changes in surface area, canal volume, dentin thickness, canal angulation, structure model index, canal transportation, and centering ability ratio. Data were analyzed using IBM SPSS Statistics for Windows, Version 23.0 (IBM Corp., Armonk, NY), with a statistical significance set at P ≤ 0.05. Micro-CT analysis demonstrated comparable untouched canal surface areas and changes in surface area and volume between both RM and WG systems. Both systems effectively straightened canal curvature without significant differences in canal angulation. The RM files exhibited a statistically lower reduction in dentin thickness, indicating better preservation of structural integrity. Both RM and WG files displayed similar effective shaping abilities. However, RM caused less dentin removal and canal transportation. Thus, RM is recommended for its ability to balance effective canal shaping with structural preservation in a conservative manner.